Vernacular universals and language contacts [ evidence from varieties of English and beyond - Filppula, Markku; Klemola, Juhani; Paulasto, Heli (New York : Routledge, 2009)
Discusses the role of two major factors shaping the grammars of different varieties of English (and of other languages) all over the world: so-called vernacular universals and contact-induced change. This book focuses on putative universal vernacular features
1. Cognition and the linguistic continuum from vernacular to standard -- 2. Vernacular universals and angloversals in a typological perspective -- 3. How diagnostic are English universals? -- 4. Number agreement in existential constructions : a sociolinguistic study of eighteenth-century English -- 5. There 'was' universals : then there 'weren't' : a comparative sociolinguistic perspective on 'default singulars' -- 6. Irish daughters of northern British relatives : internal and external constraints on the system of relativisation in South Armagh English (SArE) -- 7. The case of Bungi : evidence for vernacular universals -- 8. The regularisation of the hiatus resolution system in British English : a contact-induced 'vernacular universal'? --
9. The interplay of 'universals' and contact-induced change in the emergence of new Englishes -- 10. Digging for roots : universals and contact in regional varieties of English -- 11. Methods and inferences in the study of substrate influence -- 12. Some offspring of colonial English are Creole -- 13. Vernacular universals and the sociolinguistic typology of English dialects -- 14. Linguistic universals and vernacular data -- 15. Why universals versus contact-induced change?
"This Overview and all the other articles in this volume are based on papers presented at an international symposium on World Englishes: Vernacular Universals vs Contact-Induced Change, held at the University of Joensuu Research Station at Mekrijearvi
Description based on print version record
Includes bibliographical references and indexes
Keywords: English language -- Variation; Languages in contact; Linguistic change; Linguistic universals